CXCR1 and CXCR2 are potential neutrophil extracellular trap-related treatment targets in ulcerative colitis: insights from Mendelian randomization, colocalization and transcriptomic analysis - Xv, Yichuan; Feng, Yiyi; Lin, Jiang (Frontiers in Immunology, 2024)
Objectives: There is already substantial evidence indicating that neutrophil extracellular trap (NET) formation contributes to the inflammatory cascade in ulcerative colitis (UC). However, the precise regulatory mechanisms governing this process remain elusive. This study aimed to determine the role of NET-related genes in UC and reveal possible mechanisms.Methods: Employing a two-sample MR methodology, we investigated the correlations between NET-associated genes (NRGs) and UC with summary data derived from a genome-wide association study (12,366 cases vs. 33,609 controls) and FinnGen (8,279 cases vs. 261,098 controls). The main analysis employed the inverse variance weighted method, supplemented by the MR-Egger method and weighted median method. Sensitivity analysis was conducted to rule out the interference of heterogeneity and pleiotropy among utilized instrument variables. The colocalization analysis was used to determine whether the identified NRGs and UC shared casual variants. Cross-tissue expression analysis was performed to characterize the expression patterns of target NRGs, while multi-gene correlation analysis and GSEA analysis were conducted to explore the mechanisms by which target NRGs promote UC and NET formation. Immunohistochemistry was used to validate the protein expression of target NRGs in the colon tissue of UC patients.Results: After the validation of two datasets, seven NRGs were associated with the risk of UC. The higher expression of ITGB2 was associated with increased UC risk, while the expression of CXCR1, CXCR2, IRAK4, MAPK3, SIGLEC14, and SLC22A4 were inversely associated with UC risk. Colocalization analysis supported the correlation between CXCR1/2 and UC risk. Expression analysis indicated that CXCR1/2 were down-regulated in peripheral blood, but up-regulated in colon tissue.GSEA analysis and correlation analysis indicated that CXCR1/2 promoted UC and NET formation through neutrophil chemotaxis and PAD4-mediated pathways, separately. Immunohistochemical results confirmed the high expression of CXCR1/2 in colon tissues of UC patients.Conclusions: Our study identified CXCR1/2 as candidate targets in UC among all NRGs through multi-method argumentation, providing new insights of the regulation mechanisms of NET formation in the pathogenesis of UC.